The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1128/aem.72.5.3550-3557.2006
|View full text |Cite
|
Sign up to set email alerts
|

Auxofuran, a Novel Metabolite That Stimulates the Growth of Fly Agaric, Is Produced by the Mycorrhiza Helper Bacterium Streptomyces Strain AcH 505

Abstract: The mycorrhiza helper bacterium Streptomyces strain AcH 505 improves mycelial growth of ectomycorrhizal fungi and formation of ectomycorrhizas between Amanita muscaria and spruce but suppresses the growth of plant-pathogenic fungi, suggesting that it produces both fungal growth-stimulating and -suppressing compounds. The dominant fungal-growth-promoting substance produced by strain AcH 505, auxofuran, was isolated, and its effect on the levels of gene expression of A. muscaria was investigated. Auxofuran and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
126
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 47 publications
2
126
0
Order By: Relevance
“…AcH505 was shown to have a pronounced effect on the organization of the cytoskeleton of the ectomycorrhizal fungus Amanita muscaria (351). The same strain also produces auxofuran, a metabolite that contributes to its growth-promoting effect, the synthesis of which is promoted in bacterial-fungal cocultures and at acidic pH values that typify the growth conditions of ectomycorrhizal fungi (323).…”
Section: Consequences Of Bacterial-fungal Interactions For Participatmentioning
confidence: 99%
See 1 more Smart Citation
“…AcH505 was shown to have a pronounced effect on the organization of the cytoskeleton of the ectomycorrhizal fungus Amanita muscaria (351). The same strain also produces auxofuran, a metabolite that contributes to its growth-promoting effect, the synthesis of which is promoted in bacterial-fungal cocultures and at acidic pH values that typify the growth conditions of ectomycorrhizal fungi (323).…”
Section: Consequences Of Bacterial-fungal Interactions For Participatmentioning
confidence: 99%
“…strain AcH505 also leads to the suppression of bacterial antibiotic production. In this case, the fungus represses the biosynthesis of the antibiotics WS-5995 B and WS-5995 C by organic acid production (323). Signaling-based interactions.…”
Section: Bacterial-fungal Molecular Interactions and Communicationmentioning
confidence: 99%
“…flavonoids (AMF) and furans (ECM), that facilitate the growth of fungal hyphae and the subsequent colonization of plant roots by ECM (Founoune et al 2002;Duponnois and Plenchette 2003;Aspray et al 2006;Riedlinger et al 2006) and AM fungi (Duponnois and Plenchette 2003;Hildebrandt et al 2002Hildebrandt et al , 2006. Hildebrandt et al (2002Hildebrandt et al ( , 2006 have demonstrated that certain compounds (including raffinose and other unidentified metabolites) produced by strains of Paenibacillus can directly enhance the growth of AMF extraradical mycelium.…”
Section: Mechanism 1: Biochar Changes Soil Nutrient Availabilitymentioning
confidence: 99%
“…Two further metabolites did not correspond to any of the 834 reference compounds stored in our database. One of them was identified as anhydroSEK4b (3) [5], the second was named fogacin (1).…”
mentioning
confidence: 99%